Diversity of Bird Species in Some Land Use Around the Area of Mount Argopuro, Probolinggo - Nirmala Ayu Aryanti; Ari Prabowo; Samsul Ma’arif (Biotropika: Journal of Tropical Biology, 2018)
The land use in Argopuro Mountain is very diverse but not much information on the existence of wildlife, especially bird species that important role in helping the regeneration of natural forests and has not been documented its existence. The purpose of this study to determine the diversity of bird species in some land use around the area of Mount Argopuro. Data collection of species and number of birds using stratified systematic sampling with point counts method on each land use planted forest, protected forest, mountain rainforest, savanna and pine forest in the area of Argopura Mountain. Data analysis was done to calculating the diversity index of Shannon bird species. Medium index diversity of bird species was found in planted forest (2.6) and protected forest (2.48); the lowest in the pine forest (1.64), the mountains rainforest (1.96) and savanna (0.68).